Advances Toward Forming Synthetic Mimetic Tendon. Issue 18 (11th April 2016) - Aishanjiang, Dilinazi; Green, Emily C.; Li, Heng; Minus, Marilyn L.
ABSTRACT: Collagen is the most abundant protein present in the human body and found in connective tissues, bone, and tendon. It is also known as a natural resource for healing damaged skin tissues [1]. In this study, under specific microenvironment conditions, mimetic collagen gels were successfully formed synthetically from reconstituted Bovine type I collagen monomers. This was achieved by controlling ionic strength, temperature and pH, allowing fibrils with native mimetic D periodic banding structure to assemble spontaneously within the gels. In addition, by providing appropriate aging temperatures and times, mature collagen fibril growth is also realized in the gels in vitro . Mimetic gels were subsequently formed into fibers through a wet-spinning process. These spun fibers were found to preserve the native mimetic D periodic banding and fibrillar structure formed in the initial gels. As a result, the synthetic fibers resemble native tendon. Here structural development within the gel samples and fibers as a function of processing was analyzed by scanning electron microscopy (SEM). Results in this study also show a potentially new route for the fabrication of synthetic collagen fibers mimicking tendon, which may find applications as engineered tissues or scaffolding materials.